Book Review of Small-town America: Finding Community, Shaping the Future by R. Wuthnow - Patricia L. Hardre (Journal of Research in Rural Education, 2017)
Robert Wuthnow's Small-Town America: Finding Community, Shaping the Future is an easy read that belies the importance and complexity of its content. From the start of this book, Wuthnow lays out contrasts in perspective of current and historic issues that shape small towns in the United States. He off ers an inside perspective on small and rural communities, with a craft for framing questions clearly, and even provocatively.